OPTN/SRTR 2020 Annual Data Report: Kidney. (10th March 2022) - Lentine, K. L.; Smith, J. M.; Hart, A.; Miller, J.; Skeans, M. A.; Larkin, L.; Robinson, A; Gauntt, K.; Israni, A. K.; Hirose, R.; Snyder, J. J.
Abstract: The year 2020 presented significant challenges to the field of kidney transplantation. After increasing each year since 2015 and reaching the highest annual count to date in 2019, the total number of kidney transplants decreased slightly, to 23642, in 2020. The decrease in total kidney transplants was due to a decrease in living donor transplants; the number of deceased donor transplants rose in 2020. The number of patients waiting for a kidney transplant in the United States declined slightly in 2020, driven by a slight drop in the number of new candidates added in 2020 and an increase in patients removed from the waiting list owing to death‐important patterns that correlated with the COVID‐19 pandemic. The complexities of the pandemic were accompanied by other ongoing challenges. Nationwide, only about a quarter of waitlisted patients receive a deceased donor kidney transplant within 5 years, a proportion that varies dramatically by donation service area, from 14.8% to 73.0%. The nonutilization (discard) rate of recovered organs rose to its highest value, at 21.3%, despite a dramatic decline in the discard of organs from hepatitis C‐positive donors. Nonutilization rates remain particularly high for Kidney Donor Profile Index ≥85% kidneys and kidneys from which a biopsy specimen was obtained. Due to pandemic‐related disruption of living donation in spring 2020, the number of living donor transplants in 2020 declined below annual counts over the last decade. In this context, only a small proportion of the waiting list receives living donor transplants each year, and racial disparities in living donor transplant access persist. As both graft and patient survival continue to improve incrementally, the total number of living kidney transplant recipients with a functioning graft exceeded 250, 000 in 2020. Pediatric transplant numbers seem to have been impacted by the COVID‐19 pandemic. The total number of pediatric kidney transplants performed decreased to 715 in 2020, from a peak of 872 in 2009. Despite numerous efforts, living donor kidney transplant remains low among pediatric recipients, with continued racial disparities among recipients. Of concern, the rate of deceased donor transplant among pediatric waitlisted candidates continued to decrease, reaching its lowest point in 2020. While this may be partly explained by the COVID‐19 pandemic, close attention to this trend is critically important. Congenital anomalies of the kidney and urinary tract remain the leading cause of kidney disease in the pediatric population. While most pediatric deceased donor recipients receive a kidney from a donor with KDPI less than 35%, most pediatric deceased donor recipients had four or more HLA mismatches. Graft survival continues to improve, with superior survival for living donor recipients versus deceased donor recipients.